The post-factual polity : ethical, governance, administrative, and policy crises in the disinformation era - Alibašić, Haris (Ethics in practice (Greenwich, Conn.), 2024)
In "The Post-Factual Polity: Ethical, Governance, Administrative, and Policy Crises in the Disinformation Era," Dr. Haris Alibašić presents a compelling and timely examination of the intricate challenges facing our society in the age of disinformation and misinformation. This groundbreaking book delves into the critical intersection of ethics, governance, and the pervasive influence of post-factual politics, offering a nuanced understanding of the issues that shape public policy and administration in the digital era. Haris Alibašić, with his extensive experience and scholarly insight, guides readers through the complexities of ethical governance amidst the rise of disinformation. His insightful analysis, covering topics from the history of factual politics to the role of AI in public discourse, is essential for academics, policymakers, and anyone invested in the future of ethical governance. This book is a beacon for those seeking to navigate and counteract the challenges of misinformation, aiming to foster a more informed, ethical, and resilient society.The Post-Factual Polity is more than a book; it is an urgent call to action, a roadmap for navigating the tumultuous landscape of modern governance, and a testament to the power of truth in an era of uncertainty. As an authoritative source in the field, it is poised to become a vital reference for those dedicated to upholding the principles of democracy and integrity in public policy and administration.